PENGARUH TATA KELOLA PERUSAHAAN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada tahun 2017-2019) - Yumiko Violita Sitorus; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2022)
This research aims to examine the effect of corporate governance and institutional ownership on earnings management in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019 variabel used in the examination are board independence, board gender diversity, institutional ownership and audit committee as the independence variables, also earnings management as the dependent variable. This research used manufacturing companies during the 2017-2019 with a total sample is 303 samples. Sample based on purposive sampling method that follows certain criterias. Multiple regression analysis is the analysis method used in this research. The result of this research indicates that board independence, board gender diversity, institutional ownership and audit committee has a significant negative effect on earnings management.